An Analysis of Supply Chain Collaboration in Chinese Cement Industry: A Case Study of CereCo - Wang, Zhen (2011)
Market-driven supply chains and intense competitions require the collaboration among various supply chain (SC) participants to foster access to in-depth knowledge and complementary resources of every stage in SC. This dissertation is a case study about CereCo (the firm’s real name has been disguised), a cement manufacturer in China to discuss the issues of supply chain collaboration (SCC) in Chinese cement industry. As suppliers of coal and fly ash are also its customers, CereCo’s 3-tier SC has fewer participants compared with other companies and industries, which provides a simple background of SCC in reality. The purpose of the research is to explore how SCC helped a cement manufacturer in China, in details, the way to perform SCC, and costs decreased because of SCC.